Lokakarya Pembuatan Buku Cerita Tema Matematika Bagi Guru Sekolah Dasar - Syafri, Fatrima Santri; Aisya, Feity; Ramadanniya, Dela Nupita (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Education in Indonesia plays a crucial role in shaping children’s character and skills, and numeracy literacy is an important aspect in this process. A workshop on creating mathematical picture story books for teachers at Fatma Kenanga Elementary School was held to provide solutions to the challenges of creating an engaging literate learning environment. Mathematical picture story books are recognized as an effective tool for developing numeracy literacy skills and stimulating children’s critical thinking skills. However, the difficulty teachers have in finding mathematical picture story books that meet the criteria of the reading level motivated the holding of this workshop. The workshop aimed to provide understanding and skills to teachers at Fatma Kenanga Elementary School in creating mathematical picture story books that meet the needs of children. Through the PAR method, this workshop provided practical and creative guidance for teachers. The results showed an increase in teacher creativity in designing stories, applying simple illustration techniques, and integrating moral values into picture stories and producing mathematical picture story books. Although the workshop provided a strong foundation, some teachers felt the need for further development. Recommendations for follow-up include additional workshops, individual coaching, and online resources to continue improving teacher skills. In conclusion, this workshop made a positive contribution in supporting teachers of Fatma Kenanga Elementary School in creating a positive and engaging literacy learning environment.